Implementation Of Patient-Centered Care as An Effort to Enhance Service Quality and Patient Safety in Community Health Centers - Harniati, Harniati; Masriadi, Masriadi; Rahman, Abdul; Fadliyah, Fadliyah; Arjang, Arjang; Ambar, Sriyanti (Universitas Tribhuwana Tunggadewi, 2026)
Patient safety is a fundamental determinant in the contemporary healthcare quality assurance framework. Although the accuracy of incident reporting in Primary Health Care Facilities (FKTP) in Indonesia still faces data challenges, the urgency of clinical risk mitigation remains a strategic priority in service quality transformation. The “X” Community Health Center in Makassar integrates patient safety standards as an essential instrument for quality improvement, as mandated by the national health regulatory framework to ensure comprehensive patient protection. The study investigates whether applying patient-centered care in community health centers can improve healthcare quality and reduce risk of errors for patients at the “X” Community Health Center in Makassar. This research employs a qualitative approach with data collection techniques including participatory observation, in-depth interviews, and documentation study. The population in this study includes patients who receive health services at community health centers during the research period. They are the main parties who experience and implement patient-centered care, so they can evaluate its impact on service quality and patient safety. The sample is a subset of the population selected to represent the whole population. The sample represents both perspectives patients as service recipients and health workers as service providers. (patients from several community health centers and healthcare workers (doctors, nurses, and other staff). The total sampel in this research is 7 recipients. The study locus is the “X” Community Health Center in Makassar, with data collection occurring from November to December 2025. Data analysis indicates that the internalization of patient safety efforts at the “X” Community Health Center in Makassar has been aligned with FKTP accreditation instruments. However, empirical findings still reveal discrepancies in the realization of standards due to managerial and resource constraints. This condition suggests the need for systemic optimization and strengthening of a patient safety culture that involves all stakeholders to reduce existing operational barriers. The provision of safe and quality services is an essential prerequisite for achieving indicators of a healthy community. The acceleration of patient safety standards fulfillment at the Community Health Center must be consistently implemented, referring to the latest regulations, to ensure the sustainability of basic healthcare quality improvement.